QUALITY SERVICE PROVISION AND EFFECTIVE MANAGEMENT OF STAFF DEVELOPMENT IN THE HOTEL AND RESTAURANT BUSINESS - Rumiantseva , I.B.; Malovana , О.G. (The actual problems of regional economy development, 2025)
The article examines the quality of service provision and effective management of personnel development in the hotel and restaurant business. The definition of the concept of "personnel development" by various scientists is considered. It is substantiated that quality services provided and improvement of personnel development management in the hotel and restaurant business will positively affect the effective management of the activities of hospitality enterprises. The purpose of the article is to study the process of developing human resources management in the hotel and restaurant business and the quality of services provided by hospitality workers. In solving the tasks set, we used a number of research methods: including the analysis of literary sources to gain a deeper understanding of the topic; methods of analysis and synthesis, comparative characteristics regarding the problems of providing quality services from employees of the hotel and restaurant business and effective management of personnel development in hospitality establishments. It has been established that the quality of functioning of any hospitality establishment is primarily determined by the level of development of its employees and the quality of services provided. In today's conditions of rapid obsolescence of theoretical knowledge, skills, and practical abilities, the ability of hotel and restaurant establishments to constantly improve the level of quality services through the effective work of their employees is one of the most important factors in ensuring the competitiveness of hospitality enterprises in the modern services market. Among the components of personnel development in the hotel and restaurant business, personnel search, personnel adaptation, professional training, assessment and certification, professional career planning in the hospitality sector, as well as stimulating personnel development are highlighted. The importance of developing human resources management, which in turn improves the quality of work of hospitality enterprises, is indicated. It is noted that the success of the service sector requires the provision of quality services and continuous attention and efforts to manage the development of hotel and restaurant business employees. The use of modern training programs for effective management and high-quality provision of services by personnel in the hotel and restaurant business is proposed, as well as developing targeted training programs for hospitality businesses.